Comparison of Onset Time between 0.5% Bupivacaine and 3% 2-Chloroprocaine with and without 75 μg Fentanyl. Issue 4 (July 1991) - Johnson, Calvin; Ransil, Bernard J.; Oriol, Nancy
Abstract : We tested the hypothesis that the addition of 75 μg fentanyl to 0.5% bupivacaine would reduce the onset time of surgical anesthesia for cesarean delivery to equal the onset time of 3% 2-chloroprocaine and would have no effect when added to 3% 2-chloroprocaine. Fentanyl was found to reduce the onset time of bupivacaine to equal the onset time of 2-chloroprocaine and have no effect when added to 2-chloroprocaine.